The Aerosol OT + n-butanol + n-heptane + water system: Phase behavior, structure characterization, and application to Pt70Fe30 nanoparticle Synthesis - Malheiro, Arthur R. [UNESP]; Varanda, Laudemir C. [UNESP]; Perez, Joelma [UNESP]; Villullas, H. Mercedes [UNESP] (Amer Chemical Soc, 2007)
A phase diagram of the pseudo-ternary Aerosol OT (AOT) + n-butanol/n-heptane/water system, at a mass ratio of AOT/n-butanol = 2, is presented. Conductivity measurements showed that within the vast one-phase microemulsion region observed, the structural transition from water-in-oil to oil-in-water microemulsion occurs continuously without phase separation. This pseudo-ternary system was applied to the synthesis of carbon-supported Pt 70Fe30 nanoparticles, and it was found that nanoparticles prepared in microemulsions containing n-butanol have more Fe than those prepared in ternary microemulsions of AOT/n-heptane/water under similar conditions. It was verified that introducing n-butanol as a cosurfactant into the AOT/n-heptane/water system lead to complete reduction of the Fe ions that allowed obtaining alloyed PtFe nanoparticles with the desired composition, without the need of preparing functionalized surfactants and/or the use of inert atmosphere. © 2007 American Chemical Society.
Keywords: Microemulsions; Molecular structure; Phase behavior; Phase diagrams; Phase separation; Surface active agents; Synthesis (chemical); Microemulsion region; Structural transitions; Structure characterization; Ternary microemulsions; Ternary systems